PENERAPAN TEKNOLOGI LAHAN BASAH RETENSI UNTUK MENGATASI BENCANA KEKERINGAN DI KELURAHAN BINTORO JEMBER - Galuh, Senki Desta; Mufarida, Nely Ana; Umarie, Iskandar (Universitas Mataram, 2024)
In 2023, 103 families in Bintoro Village experienced the most severe water crisis. Meanwhile, hundreds of other families experienced moderate drought impacts. The rest of the population in Bintoro Village, Patrang Subdistrict, experienced moderate drought. The aim of this activity is that the community of Bintoro Village, Patrang Subdistrict, Jember Regency has the expertise or skills to apply wet retention pond technology to overcome drought. The activities of this Community Service program began with observation and coordination, then socialization of retention wetland technology and simulation of the application of retention wetland technology. To measure the ability of participants, an evaluation of the success of the program is carried out. After all the activities are running, a re-assessment is carried out. The average score obtained was 82.5. This value also shows that the error rate is below 20 percent. Therefore, it can be concluded that after being given training, the participants have succeeded or have been able to work on the six indicators of making retention wet ponds. The results of the assessment of the participants can be concluded that the participants have succeeded or are able to work on the six indicators of making wet retention ponds with an error rate below 20 percent.